Strategi Pemasaran Kosmetik pada Toko Gadjah Mada untuk Meningkatkan Penjualan - Shinta Kumalasari; Rusdi Hidayat (CV. Syntax Corporation Indonesia, 2021)
This research was conducted at Gadjah Mada Shop on Jl. A.Yani No.72, Regency Jombang which is engaged in the retail business that sells cosmetic brands as the object of research. The purpose of this study was to determine and analyze marketing strategies to increase sales of wardah cosmetic products at Gadjah Mada Stores. The research method used is descriptive qualitative by using in-depth interview data collection techniques on owners, employees, consumers and customers, which are related to marketing strategies based on 4P marketing mix indicators (product, price, place, promotion), participatory observation. and documentation.From the results of research using SWOT, it can be concluded that Gadjah Mada Jombang Shop is in quadrant II position. This position is ST, ST uses strength to overcome threats, so that the SWOT diagram is located in Quadrant II, that is, the company has a big threat but there are strengths from the internal side of the company so that the strategy that must be determined is to use strength that takes advantage of long-term opportunities by means of strategy diversification in products or markets.